Just Membership: Between Ideals and Harsh Realities - Shachar, Ayelet (Les ateliers de l'éthique / The Ethics Forum, 2012)
In this paper, Ayelet Shachar begins by restating the main idea of her important book The Birthright Lottery : Citizenship and Global Inequality (Harvard, Harvard University Press, 2009) and then goes on to address in a constructive spirit the main themes raised by the five preceding comments written by scholars in the fields of law, philosophy and political science.